(3QSGdI JbdjO GdCejQ GdeMGeO cajd GdehMOjf CHj GdahGQS eYVGO Hf jhSas - (3jMji Hf MeRI Hf Ydj Hf EHQGgje, GdMSjfj GdYdhqj GdWGdHj , GdeDjO HGddg , J (B745 (3g`s
(3ChdgG (B:s
(3JhcdJ Ydi Gdehdi GdEdg GdMGce GdeJYGdi Yf GdehgeGJ hGdefRg Yf GdJMOjO hGdfYJ hGdUaGJ ef GdYHO GdWGFY GdNGVY QGjY GdCYOGO s
(3BNQgG (B:s
(3hCfG CSJhOYc ddMajX GdMGce GdYGde hGdMeO dehdGfG GdMGce hMOg hGdTcQ ddEeGe GdbGFe GdgGOi YHOg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B48s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ , RNGQa s
Keywords: (3GdJhMjO hGdedd hGdfMds